The Russian revolution of 1905 and the Chinese intellectuals - White, J.D. (Sibirica: Journal of Siberian Studies, 2002)
The article examines the reception of the Russian revolutionary movement and the revolution of 1905 by Chinese reformers and revolutionaries. It reveals how events in Russia were refracted through the imperatives of the Chinese political situation and used to support indigenous political attitudes. It also brings to light relationships between Russian, Chinese and Japanese history which are not apparent when these countries are studied individually.